2018
DOI: 10.1111/zph.12530
|View full text |Cite
|
Sign up to set email alerts
|

Cattle‐associated risk factors for human tuberculosis in rural livestock‐keeping communities, Uganda

Abstract: Tuberculosis (TB) is a leading infectious cause of human death worldwide. In cattle, TB infection results in productivity losses, trade barriers and zoonotic transmission via milk, meat or direct contact. We conducted a cross‐sectional study in rural communities in Uganda between 2014 and 2016 to evaluate the association between tuberculosis skin test (TST) positivity in humans and cattle‐associated risk factors: household herd positivity and raw milk consumption. Human and cattle TSTs were performed in commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Consistent with our findings, a study of cattle-owning families in Uganda found that having at least one TST (tuberculin skin test)positive bovine in the household cattle herd was associated with a lower TST positivity among men (prevalence ratio (PR) = 0.66, 95% CI: 0.49, 0.87), but not among women (PR = 1.21, 95%CI: 0.76, 1.95) (Meisner et al, 2019). Traditionally, in Uganda, men look after the cattle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, a study of cattle-owning families in Uganda found that having at least one TST (tuberculin skin test)positive bovine in the household cattle herd was associated with a lower TST positivity among men (prevalence ratio (PR) = 0.66, 95% CI: 0.49, 0.87), but not among women (PR = 1.21, 95%CI: 0.76, 1.95) (Meisner et al, 2019). Traditionally, in Uganda, men look after the cattle.…”
Section: Discussionsupporting
confidence: 90%
“…There is some evidence that living closely with cattle may be a risk factor for pulmonary tuberculosis (PTB) (Mfinanga et al, 2003;Waziri et al, 2014); however, other evidence suggests that close contact with Mycobacterium bovis-infected cattle may have a protective association with TB in cattle herders (Berg et al, 2015;Meisner et al, 2019). Some illnesses attributed to M. tuberculosis, particularly in high TB burden countries, are caused by M. bovis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, of the total (n = 81) references reporting on infection and morbidity outcomes, about four out of five (n = 66, 79.5%) of the references indicated that livestock keeping is strongly associated with transmission of various microorganisms and diseases in man. On the other hand, some articles (n = 13, 16%) (47,(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164) indicated a lack of association (neutral), while a few (n = 4, 4.9%) (156,(165)(166)(167) showed a protective effect (positive association) between livestock keeping and disease transmission.…”
Section: Studies On the Association Between Livestock Keeping And Inf...mentioning
confidence: 99%
“…Among bacterial species, Brucellosis (n = 8) (91,96) , Campylobacter (n = 7) (88,91,102,109,168) and Salmonella (n = 3) (90,118,119) were also mentioned as having adverse effects on man from keeping livestock. Other bacterial species including Coxiella (141) , Escherichia (118) , Enterotoxigenic bacteroides fragilis (92) , Mycobacterium tuberculosis (164) , Mycobacterium ulceran (167) and Thermotolerant coliform (TTC) (123) were also identified (Table 4).…”
Section: Studies On the Association Between Livestock Keeping And Inf...mentioning
confidence: 99%
“…Indeed, zoonotic M. bovis has been previously isolated from patients with cervical lymphadenitis in this region which emphasizes the risk of human infection with zoonotic M. bovis due to close association of humans with cattle in this region (15,17). The burden of childhood TB in Moroto district remains unreported by TB control program in their weekly bulletins.…”
Section: Introductionmentioning
confidence: 99%